Association between chronic stress and the epigenome: Exploration of psychological and biological stress - Melissa Miller; Robin D. Brown; Cole Krautkramer; Rhea Gogia; Hagen Fritz; Dennis Wylie; Kerry Kinney; Frances A. Champagne (PLoS ONE, 2026)
Chronic stress is a predictor of health outcomes. Epigenetic mechanisms such as DNA methylation (DNAm) have been proposed as mediators between stress and health trajectories, with evidence from animal models supporting a causal relationship between chronic stress and variation in the epigenome. However, when examining the impact of stress in humans, stress is often very broadly defined and includes both the perception of stress (psychological stress) and biological indices of stress such as variation in the stress hormone cortisol (biological stress). There has been limited exploration of the distinct epigenetic associations with psychological vs. biological stress or analysis of these relationships that consider genome-wide DNAm. The current study used a longitudinal design (9 weeks) with 69 healthy participants aged 18–35. Self-reported psychological stress was assessed several times a week and averaged over the 9-week period. Hair cortisol concentration (HCC) and salivary genome-wide DNAm were assessed at the end of the 9-week period. We identified epigenomic associations between chronic psychological stress (956 CpG sites) and HCC (10,335 CpG sites), with elevated chronic psychological stress generally associated with DNA hypomethylation and elevated HCC generally associated with DNA hypermethylation. Self-report stress and HCC were not correlated. DNAm at 16 CpG sites was significantly associated with both psychological stress and HCC, though in opposing directions which may suggest potential upregulation vs. downregulation of overlapping biological pathways identified in response to these stressors. Associations between stress (psychological and biological) and DNAm within stress-associated genes were observed, generally suggesting a positive association between stress and DNAm. Epigenetic age (PhenoAge) was negatively associated with psychological stress and HCC, though these relationships were sex-specific and varied based on ethnicity-race. Findings suggest unique associations between stress and the epigenome, highlighting the complex pathways through which the biological embedding of stress and subsequent stress-associated health outcomes may emerge.